miR-125b acts as a tumor suppressor in chondrosarcoma cells by the sensitization to doxorubicin through direct targeting the ErbB2-regulated glucose metabolism - Tang XY; Zheng W; Ding M; Guo KJ; Yuan F; Feng H; Deng B; Sun W; Hou Y; Gao L (Dove Medical Press, 2016)
Xian-ye Tang,1,2,* Wei Zheng,1,2,* Min Ding,3 Kai-jin Guo,1,2 Feng Yuan,1 Hu Feng,1 Bin Deng,1 Wei Sun,1 Yang Hou,4 Lu Gao5,6 1Department of Orthopedic, The First Clinical Medical College, Nanjing Medical University, Nanjing, 2Affiliated Hospital of Xuzhou Medical College, Xuzhou, Jiangsu, 3Department of Emergency Trauma Surgery, East Hospital Affiliated to Tongji University, 4Department of Orthopedic, Changzheng Hospital, Shanghai, 5College of Life Sciences, Northeast Agricultural University, Harbin, Heilongjiang, People’s Republic of China; 6Department of Pathology, University of Maryland School of Medicine, Baltimore, MD, USA *These authors contributed equally to this work Abstract: Chondrosarcoma is the second most common type of primary bone malignancy in the United States after osteosarcoma. Surgical resections of these tumors are the only effective treatment to chondrosarcoma patients due to their resistance to conventional chemo- and radiotherapy. In this study, miR-125b was found to perform its tumor-suppressor function to inhibit glucose metabolism via the direct targeting of oncogene, ErbB2. We report miR-125b was downregulated in both chondrosarcoma patient samples and cell lines. The total 20 Asian chondrosarcoma patients showed significantly downregulated miR-125b expression compared with normal tissues. Meanwhile, miR-125 was downregulated in chondrosarcoma cells and doxorubicin resistant cells. Overexpression of miR-125 enhanced the sensitivity of both parental and doxorubicin resistant cells to doxorubicin through direct targeting on the ErbB2-mediated upregulation of glycolysis in chondrosarcoma cells. Moreover, restoration of the expression of ErbB2 and glucose metabolic enzymes in miR-125 pretransfected cells recovered the susceptibility to doxorubicin. Our study will provide a novel aspect on the overcoming chemoresistance in human chondrosarcoma cells and may help in the development of therapeutic strategies for the treatments of patients. Keywords: miR-125b, chondrosarcoma, doxorubicin, glucose metabolism, sensitization